The Improvement of Indonesian Language Learning Outcomes in Poetry Writing Materials Through the Real Experience Method for Year VIII-A Students of Madrasah Tsanawiyah Negeri 3 West Aceh in the 2021/2022 Academic Year - Hardianto, Suji (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
This study aims to determine